Patterns of Islamic Education in Child Care Services in Kejapanan Village, Gempol District, Pasuruan Regency - Mardhiana Amalia Dessy Fadzrina Ilham; Budi Hariyanto (Indonesian Journal of Islamic Studies, 2021)
This research is a descriptive research type, and the type of approach used is qualitative. In the book by Sukmadinata, it explains that "Descriptive research with a qualitative approach is a descriptive qualitative narrative of the situation". A qualitative approach is research which will then produce the results of analytical procedures that do not use statistical analysis studies. The main objective of the research is obtain data, therefore the main step that must be taken in a study is data collection. In Kejapanan village there are several day care centers for children among others, a day care center that is cared for by Mrs. Sriati and a day care center that is cared for by Ms. Safa'ah. In Mrs. Safa'ah's daycare, there were no signs of education for children related to Islamic values, whereas where there is a form of education for children based on Islamic values with the form of teaching daily prayers, singing Islamicsongs.